Factors Associated with Readiness to Adopt Electronic Health Record in Professional Health Workers: A Meta-Analysis - Wibawa, Purwa Adrianta; Tamtomo, Didik; Murti, Bhisma (Journal of Health Policy and Management, 2024)
Background: The application of an electronic health record at a health service center is something that needs to be prepared so that such a system can be successful. This study aims to determine the factors that influence the readiness of EHR adoption among health professionals. Subject and Method: This systematic review and meta-analysis was carried out using the PRISMA guidelines and the PICO model: Population: professional health workers, intervention: computer literate, computer access, high perceived benefit, high self-efficacy, EHR training, technical assistance, comparison: no computer literacy, no computer access, no perceived benefit, low self-efficacy, no EHR training, no technical assistance, outcome: readiness to adopt EHR. Articles are collected from databases like Pubmed, Google Scholar, Science Direct. The keywords used are "electronic health record" OR “EHR” OR “electronic medical record” OR “EMR” OR “electronic patient record” OR “EPR” AND “adoption” OR “readiness” AND “EHR implementation” AND “healthcare professionals “AND “Multivariate analysis”. A total of 13 articles met the inclusion criteria, namely full text articles with a cross-sectional study design, with a relationship size adjusted odds ratio (aOR). Data were analyzed using RevMan 5.3. Result: Meta-analyses from Myanmar, Saudi Arabia, Ghana, Ethiopia, the Netherlands, and the United States showed that computer literacy (aOR= 1.67; CI 95%= 1.29 to 2.16; p< 0.001), computer access (aOR= 1.93; CI 95%= 1.41 to 2.64; p< 0.001), perceived benefit (aOR= 3.21; CI 95%= 2.27 to 4.56; p< 0.001), self-efficacy (aOR= 1.94; CI 95%= 1.37 to 2.75; p< 0.001), HER training (aOR= 2.20; CI 95%= 1.58 to 3.06; p< 0.001), and technical assistance (aOR= 2.34; CI 95%= 1.26 to 4.35; p= 0.007) influenced in the readiness of EHR adoption in health professionals and it was statistically significant. Conclusion: Good computer literacy, computer access, high perceived benefits, high self-efficacy, EHR training, and technical support increased the readiness for EHR adoption among professional health workers. Keywords: electronic health record, EHR, medical records, health services, professional health workers. Correspondence: Purwa Adrianta Wibawa. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Email: purwaadrianta@gmail.com. Mobile: +62 821-3269-7209.